The Implementation of Case Study Method to Develop Students’ Activities and Characters - Agung Nugroho; Dhi Bramasta (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
ABSTRACT Learning activities are carried out to result in a development of knowledge, behavioral values, and skills of students as a deliberate practice. These activities will result in knowledge and skills leading to the improvement of students’ learning results. This study was aimed at implementing cooperative learning model through case study method as an attempt to direct and develop students’ learning activities as well as develop cooperative character to support learning and teaching activities. The subjects were fourth year students of UMP elementary school. The study covered 2 cycles consisting of 2 meetings for each cycles. Each meeting employed three steps consisting of Plan, Do, See. The result showed that case study method is considered effective to develop activities and cooperative characters of students. The lesson study activity was conducted as planned and able to influence the quality of learning process significantly.